Development of stability-indicating HPLC method for quantification of pharmacopeia impurities of Zuclopenthixol and characterization of its stress degradation products by LCMS/MS - Bondili Sesharamsingh; J. Suresh Kumar; I. V. Kasi Viswanath; Gattupalli Subhakara Rao; Venkateswara Rao Anna (SpringerOpen, 2023)
Abstract Background The present study focused to develop a simple and sensitive HPLC method for resolution and estimation process-related impurities of zuclopenthixol and further assessment of forced degradation behavior of zuclopenthixol. Results The chromatographic separation of drug substance, process-related impurities and its degradation products (DPs) was achieved on KNAUER C18 (250 mm × 4.6 mm, 5µ id) column at that was maintained at 35 °C temperature using 0.1 M sodium acetate buffer at pH 4.3 and methanol in 20:80 (v/v) as mobile phase A, 0.1% formic acid and acetonitrile in 75:25 (v/v) as mobile phase B. Equal volume of mobile phase A and B was pumped in isocratic elution at 0.8 mL/min. Detection wavelength was selected as 257 nm. In the proposed conditions, zuclopenthixol is identified at 6.91 and 1.91 min and 2.89 min, respectively, for impurity B and A min with acceptable system suitability and specificity. The method produces LOD at 0.009 for impurities with calibration range of 30-180 µg/mL for zuclopenthixol and 0.03-0.18 µg/mL for impurities. The other validation parameters were notices to be with in the acceptable levels for zuclopenthixol and its impurities. The drug was exposed to different stressed conditions (acid, base, peroxide, thermal and UV light) according to ICH Q1A (R2) guidelines. The DPs formed during the stress study were identified and characterized by LCMS/MS in ESI positive mode. Conclusion The analysis involved a comparison of collision-induced dissociation mass spectrometry data between the degradation products and zuclopenthixol. As a result, potential structures for six degradation compounds were suggested. The results from additional validation studies were similarly pleasing and demonstrated their suitability for the routine analysis of zuclopenthixol and its associated impurities in both bulk drug and pharmaceutical dosage forms. Additionally, these findings can be extended to assess the mechanism of stress degradation in zuclopenthixol.